2021
DOI: 10.2147/cia.s280808
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Hyperglycemia Ratio is Associated with Hemorrhagic Transformation in Patients with Acute Ischemic Stroke

Abstract: Background Hemorrhagic transformation (HT) is a severe complication occurring in acute ischemic stroke (AIS) patients. Stress hyperglycemia is frequent in patients with acute illness such as stroke. We aimed to explore the association between stress hyperglycemia and HT in AIS patients. Methods A total of 287 consecutive participants with HT and 285 age- and sex-matched stroke patients without HT were enrolled in this study. Baseline glucose and glycated hemoglobin (HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 53 publications
3
45
1
1
Order By: Relevance
“…However, Hempe et al (2010) pointed out that the term “eAG” should be used carefully for clinical practice due to discrepancies between eAG and self-monitored mean blood glucose. Another definition of SHR using the glucose/HbA1c ratio was more practical and widely applied in many studies ( Zhu et al, 2019 ; Li et al, 2020 ; Merlino et al, 2020 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hempe et al (2010) pointed out that the term “eAG” should be used carefully for clinical practice due to discrepancies between eAG and self-monitored mean blood glucose. Another definition of SHR using the glucose/HbA1c ratio was more practical and widely applied in many studies ( Zhu et al, 2019 ; Li et al, 2020 ; Merlino et al, 2020 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under acute stress, the stress-induced hyperglycemia is a common physiological response that usually refers to transient hyperglycemia (Yuan et al 2021). In the population, stress-induced hyperglycemia occurs in approximately half of patients with acute ischemic stroke, and it is generally believed to be associated with an increased risk of death and poor neurological prognosis (Li et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study conducted in Lianyungang Hospital in China, 426 patients with anterior ischemic stroke were included and HbA1c was found to be a predictor of hemorrhagic transformation [ 13 ]. Another study conducted on 287 patients from the First Affiliated Hospital of Wenzhou Medical University showed that a high stress hyperglycemia ratio (fasting blood sugar divided by HbA1c) was significantly associated with an increased risk of hemorrhagic transformation in patients with ischemic stroke [ 15 ].…”
Section: Discussionmentioning
confidence: 99%